2011
DOI: 10.1007/s11064-011-0476-4
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Rich Saline is Cerebroprotective in a Rat Model of Deep Hypothermic Circulatory Arrest

Abstract: Deep hypothermic circulatory arrest (DHCA) has been widely used in the operations involving the aortic arch and brain aneurysm since 1950s; but prolonged DHCA contributes significantly to neurological deficit which remains a major cause of postoperative morbidity and mortality. It has been reported that hydrogen exerts a therapeutic antioxidant activity by selectively reducing hydroxyl radical. In this study, DHCA treated rats developed a significant oxidative stress, inflammatory reaction and apoptosis. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 48 publications
0
12
0
1
Order By: Relevance
“…( 12 ) Several researchers also observed that H 2 reduces oxidative DNA damage in brain tissues, indicating its potential as a neuroprotective potential. ( 26 28 ) In addition, H 2 can penetrate the blood-brain barrier, an import advantage of using H 2 over other neuroprotective drugs. ( 16 ) We have previously confirmed that maternal H 2 administration increases the H 2 concentrations in the fetal brains.…”
Section: Discussionmentioning
confidence: 99%
“…( 12 ) Several researchers also observed that H 2 reduces oxidative DNA damage in brain tissues, indicating its potential as a neuroprotective potential. ( 26 28 ) In addition, H 2 can penetrate the blood-brain barrier, an import advantage of using H 2 over other neuroprotective drugs. ( 16 ) We have previously confirmed that maternal H 2 administration increases the H 2 concentrations in the fetal brains.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, the most common injection methods of hydrogen included inhaling hydrogen gas, intravenous or intraperitoneal injecting hydrogen solution, and drinking hydrogen rich water (HRW). 11 12 13 However, the above methods may not be able to guarantee enough hydrogen concentration in certain local damage models. Shigeta et al 14 demonstrated the luminal injection of hydrogen-rich glucose saline may be a novel and promising way in a small bowel ischemic/reperfusion (I/R) injury model.…”
Section: T He I Njection M mentioning
confidence: 99%
“…6 Oxidative stress and apoptotic neuronal death signaling pathways also have been involved in the brain in patients undergoing CPB and DHCA. 7 Peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1a) is a potent stimulator of mitochondrial biogenesis and respiration, and powerfully regulates oxidative and mitochondrial metabolism in a number of tissues, including the central nerve system. 8 However, it is still not known whether PGC-1a is expressed in the brain after DHCA and functions as a regulator of oxidative stress and apoptotic neuronal death.…”
Section: See Editorial Commentary Page 684mentioning
confidence: 99%
“…A pathologic score was used to evaluate the neurologic damage: 0 ¼ no damage; 1 ¼ 0% to 12.5% damage; 2 ¼ 12.5% to 25% damage; 3 ¼ 25% to 50% damage; and 4 ¼ more than 50% damage. 7 microRNA Extraction and Quantitative Reverse Transcription Polymerase Chain Reaction Total RNA was isolated by using Trizol reagent (Invitrogen, Carlsbad, Calif) according to the manufacturer's instruction. The first-strand cDNA was generated using the Reverse Transcription System Kit (Invitrogen).…”
Section: Histologic Studymentioning
confidence: 99%